Variations in the pre-operative status of patients coming to primary hip replacement for osteoarthritis in European orthopaedic centres - Dieppe, P; Judge, A; Williams, S; Ikwueke, I; Guenther, K; Floeren, M; Huber, J; Ingvarsson, T; Learmonth, I; Lohmander, L; Nilsdotter, A; Puhl, W; et al. (BioMed Central, 2009)
Background: Total hip joint replacement (THR) is a high volume, effective intervention for hip osteoarthritis (OA). However, indications and determinants of outcome remain unclear. The 'EUROHIP consortium' has undertaken a cohort study to investigate these questions. This paper describes the variations in disease severity in this cohort and the relationships between clinical and radiographic severity, and explores some of the determinants of variation. Methods: A minimum of 50 consecutive, consenting patients coming to primary THR for primary hip OA in each of the 20 participating orthopaedic centres entered the study. Pre-operative data included demographics, employment and educational attainment, drug utilisation, and involvement of other joints. Each subject completed the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC – Likert version 3.1). Other data collected at the time of surgery included the prosthesis used and American Society of Anaesthesiologists (ASA) status. Pre-operative radiographs were read by the same three readers for Kellgren and Lawrence (K&L;) grading and Osteoarthritis Research Society International (OARSI) atlas features. Regression analyses were carried out. Results: Data from 1327 subjects has been analysed. The mean age of the group was 65.7 years, and there were more women (53.4%) than men. Most (79%) were ASA status 1 or 2. Reported disease duration was 5 years or less in 69.2%. Disease in other joint sites was common. Radiographs were available in 1051 subjects and the K&L; grade was 3 or 4 in 95.8%. There was much more variation in clinical severity (WOMAC score); the mean total WOMAC score was 59.2 (SD 16.1). The radiographic severity showed no correlation with WOMAC scores. Significantly higher WOMAC scores (worse disease) were seen in older people, women, those with obesity, those with worse general health, and those with lower educational attainment. Conclusion: 1. Clinical disease severity varies widely at the time of THR for OA. 2. In advanced hip OA clinical severity shows no correlation with radiographic severity. 3. Simple scores of pain and disability do not reflect the complexity of decision-making about who should have a THR.